Epigenetic drugs induce the potency of classic chemotherapy, suppress post-treatment re-growth of breast cancer, but preserve the wound healing ability of stem cells. Issue 1 (31st December 2022) - Zheng, Andrew; Bilbao, Michelle; Sookram, Janhvi; Linden, Kimberly M.; Morgan, Andrew B.; Ostrovsky, Olga
ABSTRACT: Epigenetic therapy augments neoadjuvant chemotherapy (NACT) in breast cancer and may aid post-surgical wound healing affected by NACT. Our study investigates: (1) The cytotoxicity of classic paclitaxel chemotherapy on triple negative breast cancer (TNBC) independently and in combination with epigenetic drugs. (2) The sustainable inhibition of breast cancer regrowth following paclitaxel and epigenetic therapies. (3) The effects of paclitaxel with and without epigenetic therapy on the post-treatment viability and wound healing potential of adipose stem cells (ASCs). Cytotoxicity assays were performed on TNBC and ASCs. Cells were treated and recovered in drug-free medium. Cell viability was measured via cell counts and MTT assays. W -ound healing was tested with scratch assays. The combination of epigenetic drugs shows increased toxicity against TNBC cells compared to standard chemotherapy alone. Moreover, the combination of paclitaxel with epigenetic treatments causes cancer toxicity that is sustainable to TNBC cells after the drugs' removal with minimal effect on ASCs wound healing ability. The use of epigenetic drugs in addition to standard chemotherapy is cytotoxic to TNBC cells and prevents post-treatment recovery of TNBC while maintaining ASC wound healing ability. This strategy may be useful in maximizing post-surgical wound healing following NACT in TNBC.